Kinetic study on alkylation of hydroquinone with methanol over SO3H functionalized Bronsted acidic ionic liquids - Bhongale, V. Priyanka; Amonkar, Amogh A.; Joshi, Sunil S.; Mali, Nilesh A. (Canadian Journal of Chemical Engineering, 2022)
O-alkylation of a dihydric phenol (i.e., hydroquinone) with methanol in presence of benzoquinone catalyzed by double SO3H functionalized Bronsted acidic ionic liquids (i.e., 1,3-disulphonic acid imidazolium hydrogen sulphate, 1,3-disulphonic acid benzimidazolium hydrogen sulphate, and sulphuric acid) is studied in a batch reactor. The sensitivity of activity and selectivity with reaction time, temperature, speed of agitation, and catalyst loading was examined. The plausible reaction pathways proposed based on the experimental observations and detailed kinetic investigation are performed by assuming a homogeneous reaction phase. The kinetic parameters, such as pre-exponential factor and activation energy, are estimated for both ionic liquids and sulphuric acid by considering all competitive reactions, and comparative results were presented. An extended form of the Arrhenius equation is used to estimate the kinetic parameters for the reaction which showed curvature in lnk against a 1/T plot. The model prediction with the estimated kinetic parameters is in good agreement with the experimental data, which confirmed the model validity in the experimental operating range. It was found that ionic liquid has a potential application in the synthesis of a selective monoalkylated product of hydroquinone. The kinetic analysis performed is found to be useful in the understanding of process behaviour.
Keywords: 4-Methoxyphenol; Hydroquinone; ionic liquids; Kinetic analysis; O-alkylation

Reusable and efficient polystyrene immobilized ionic liquid catalyst for batch and flow methylation of hydroquinone - Bhongale, V. Priyanka; Joshi, Sunil S.; Mali, Nilesh A. (Catalysis Letters, 2022)
An environmentally benign process for synthesizing 4-methoxyphenol through methylation of hydroquinone using polystyrene immobilized Bronsted acidic ionic liquid is presented. The catalyst has been characterized by several techniques, such as solid-state NMR, FTIR, and XRD. The morphological properties were analyzed through SEM and TEM analysis. The elemental analysis was performed using EDS and XPS techniques. The catalyst was thermally stable up to 603 K, which was confirmed by TGA. The chemical interaction between ionic liquid and polystyrene was confirmed by measuring the glass transition temperature of pure polystyrene and catalyst. The BET analysis was performed to estimate the catalyst's surface area, pore size, and pore volume. The recyclability of the proposed new catalyst was established up to five recycle runs in the batch mode. In addition, continuous flow experiments were conducted to test the catalytic activity in terms of catalyst life span and showed excellent stability up to 20 h. The rapid separation, long-term stability, and efficient recycling of synthesized polymeric catalysts make an excellent alternative to the commonly used homogeneous catalysts for selective O-methylation of hydroquinone reaction. The newly developed continuous process for synthesizing 4-methoxyphenol with 100% selectivity suggests good opportunities to reduce energy consumption, which designates a cost-effective process. [GRAPHICS] .
Keywords: 4-Methoxyphenol; Hydroquinone; O-methylation; Polystyrene immobilized ionic liquid